Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja pada PT. Pos Indonesia Kantor Cabang Cinere - Muhamad Saddam; Ridwan Faroji; Najibullah Najibullah; Nur Imam Duta Waskita (Prodi Manajemen STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of leadership and work environment on job satisfaction at PT. POS Indonesia Cinere Branch Office. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that leadership has a significant effect on job satisfaction by 45.3%, hypothesis testing is obtained t count > t table or (9,001 > 1,984). The work environment has a significant effect on job satisfaction by 44.2%, hypothesis testing is obtained t count > t table or (8.806 > 1.984). Leadership and work environment simultaneously have a significant effect on job satisfaction with the regression equation Y = 10,553 + 0.365X1 + 0.378X2. The influence contribution is 53.6%, the hypothesis test is obtained by F arithmetic > F table or (56.081 > 2.700).